A Chinese Contribution to Universal History, Viewed from the Future. (2nd January 2022) - Zepp-LaRouche, Helga
Abstract: The world seems to be divided at this point into two camps. If the world is to become a community with a shared future for mankind, then the growing conflict between these two camps must be overcome. China is presently the only country that has a clear, exciting vision for the future. Given its incredible record of success, especially during the last forty years, there is every reason to assume that this goal has overwhelming chances of being reached. The main problem, however, is that the proponents of the liberal system regard the Chinese model as a rival and even adversary to their own system, and they are determined to contain the further rise of China. One of the essential keys to solving the strategic dilemma is to enter into a cultural dialogue around those high points in the cultural tradition of the different cultures which did bring mankind a step further.